Implementasi Nilai-Nilai Al-Qur'an sebagai Strategi dalam Proses Pembelajaran di Pondok Pesantren Djaga Daeng Maroa - Suriyati, Suriyati; Judrah, Muh.; Mustamir, Mustamir; Wahyuningsih, Wahyuningsih; Sinta, Sinta; Aprilia, Tri (Faculty of Tarbiyah and Teacher Training, 2025)
Islamic boarding schools are Islamic educational institutions that play an important role in shaping the character of students based on the values ​​of the Qur'an. This study aims to analyze the implementation of the values ​​of the Qur'an as a strategy in the learning process at the Djaga Daeng Maroa Islamic Boarding School. The research method used is descriptive qualitative with in-depth interview techniques as the main source of data collection. Information was obtained through interviews with female teachers who were directly involved in the learning process at the Islamic boarding school. The results of the study indicate that the values ​​of the Qur'an such as honesty, responsibility, and trustworthiness are integrated into learning activities through exemplary-based teaching, strengthening the habit of worship, and thematic methods based on the Qur'an. Female teachers also emphasize the importance of these values ​​in shaping the Islamic personality of students. The challenges faced include limited resources and resistance in implementing change, but this is overcome through the development of innovative and consistent learning programs. This study concludes that female teachers provide an in-depth description of the effectiveness of the implementation of the values ​​of the Qur'an as an educational strategy at the Djaga Daeng Maroa Islamic Boarding School. These results can be a reference for the development of learning methods based on Islamic values ​​in other educational institutions.